SARS-CoV-2 in migrant worker dormitories: Geospatial epidemiology supporting outbreak management. (February 2021) - Gorny, Alexander W.; Bagdasarian, Natasha; Koh, Azriel Hong Kiat; Lim, Yong Chin; Ong, Jacqueline Soo May; Ng, Bryan Su Wei; Hooi, Benjamin; Tam, Wai Jia; Kagda, Fareed Husain; Chua, Gerald Seng Wee; Yong, Michael; Teoh, Hock Luen; et al.
Highlights: High density residential facilities showed heterogeneity in SARS-CoV-2 transmission. Geospatial epidemiology helped visualise the severity of outbreak. Real-time epidemiology guided resource allocation during outbreak management. Apartment-style buildings reduced the rate of transmission between housing units. Abstract: Background: Migrant worker dormitories—residential complexes where 10–24 workers share living spaces—account for the majority of cases of SARS-CoV-2 infection in Singapore. To prevent overspill of transmission to the wider population, starting in early April 2020, residents were confined to their dormitories while measures were put in place to arrest the spread of infection. This descriptive study presents epidemiological data for a population of more than 60 000 migrant workers living in two barracks-style and four apartment-style dormitories located in western Singapore from April 3 to June 10, 2020. Methods: Our report draws from data obtained over the first 50 days of outbreak management in order to describe SARS-CoV-2 transmission in high-density housing environments. Cumulative counts of SARS-CoV-2 cases and numbers of housing units affected were analyzed to report the harmonic means of harmonic means of doubling times and their 95% confidence intervals (CI). Results: Multiple transmission peaks were identified involving at least 5467 cases of SARS-CoV-2 infection across six dormitories. Our geospatial heat maps gave an early indication of outbreak severity in affected buildings. We found that the number of cases of SARS-CoV-2 infection doubled every 1.56 days (95% CI 1.29–1.96) in barracks-style buildings. The corresponding doubling time for apartment-style buildings was 2.65 days (95% CI 2.01–3.87). Conclusions: Geospatial epidemiology was useful in shaping outbreak management strategies in dormitories. Our results indicate that building design plays an integral role in transmission and should be considered in the prevention of future outbreaks.